Designing Feed Forward Neural Network for Solving Linear VolterraIntegro-Differential Equations - Ibraheem, L. N. M. Tawfiq, G .H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this paper, is to design multilayer Feed Forward Neural Network(FFNN)to find the approximate solution of the second order linear Volterraintegro-differential equations with boundary conditions. The designer utilized to reduce the computation of solution, computationally attractive, and the applications are demonstrated through illustrative examples.